Perceptions of Important Characteristics of Physical Activity Facilities: Implications for Engagement in Walking, Moderate and Vigorous Physical Activity - Heinrich, Katie M.; Haddock, Christopher K.; Jitnarin, Natinee; Hughey, Joseph; Berkel, LaVerne A.; Poston, Walker S. C. (Frontiers in Public Health, 2017)
Background Although few United States adults meet physical activity recommendations, those that do are more likely to access to physical activity facilities. Additionally, vigorous exercisers may be more likely to utilize a nearby physical activity facility, while light-to-moderate exercisers are less likely to do so. However, it is unclear what characteristics of those facilities are most important as well as how those characteristics are related to activity intensity. Purpose This study examined relationships between self-reported leisure-time physical activities and the use of and perceived characteristics of physical activity facilities. Methods Data were from a cross-sectional study in a major metropolitan area. Participants (N = 582; ages 18–74, mean age = 45 ± 14.7 years) were more likely to be female (69.9%), Caucasian (65.6%), married (51.7%), and have some college education (72.8%). Household surveys queried leisure-time physical activity, regular physical activity facility use, and importance ratings for key facility characteristics. Results Leisure-time physical activity recommendations were met by 41.0% of participants and 50.9% regularly used a physical activity facility. Regular facility use was positively associated with meeting walking (p = 0.036), moderate (p < 0.001), and vigorous (p < 0.001) recommendations. Vigorous exercisers were more likely to use a gym/fitness center (p = 0.006) and to place higher importance on facility quality (p = 0.022), variety of physical activity options offered (p = 0.003), and availability of special equipment and resources (p = 0.01). The facility characteristics of low or free cost (p = 0.02) and offering childcare (p = 0.028) were barriers for walking, and being where friends and family like to go were barriers for moderate leisure-time physical activity (p = 0.013). Conclusion Findings offer insights for structuring interventions using the social ecological model as well as for improving existing physical activity facilities.